GENDER PERFORMATIVITY IN THE FILM “TRUE SPIRIT” BY SARAH SPILLANE - Djailani, Sriwahyu Prasetyo; Husain, Dahlia; Mariana, Ana (LPPM STISIPOL Mujahiddin, 2024)
This research examines the gender performativity displayed by the female main character in the film